Carbon quantum dot-ferric oxide nano composite material as well as preparation method and application thereof

By using carbon quantum dot-iron oxide nanocomposites, the existing VOCs oxidation catalysts are solved, and the effect of efficient removal of indoor VOCs at room temperature is achieved, and the materials are economical and environmentally friendly.

CN119386870APending Publication Date: 2025-02-07DONGYANG JIPEI ADVANCED MATERIALS & DEVICES RESEARCH INSTITUTE
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411507332.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing VOCs oxidation catalysts have problems such as high cost, low efficiency and environmentally harmfulness, and traditional removal methods are difficult to meet the practical application needs.

Method used

采用碳量子点-氧化铁纳米复合材料,通过沸石咪唑酯骨架结构材料合成具有复杂框架、高比表面积、高催化活性的氧化铁,并与5-8nm尺寸的石墨烯碳量子点进行复合,使 It can efficiently oxidize indoor VOCs at room temperature.

Benefits of technology

83.5±4.3% of the VOCs in the test chamber can be removed within 24 hours, which significantly improves the VOCs removal efficiency, and the materials are economical and environmentally friendly, avoiding the increase in by-products and health risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a carbon quantum dot-ferric oxide nano composite material as well as a preparation method and application thereof. The composite material is prepared by the following steps: S1, mixing a ferrous sulfate solution with an imidazole methanol solution, and performing ultrasonic treatment to obtain a zeolite imidazate skeleton structure material containing an iron core; s2, calcining the zeolite imidazate skeleton structure material in an environment with a temperature range of 200-700 DEG C and oxygen partial pressure of 5-40% to obtain iron oxide with a complex frame structure; s3, synthesizing graphene carbon quantum dots with the size of 5-8 nm by adopting a trinitrophenol method; s4, the carbon quantum dots and ferric oxide powder are mixed and then evenly ground in a ball mill, the ball milling time is 60-240 min, the content of the added graphene carbon quantum dots is 0.5-3 wt%, and a carbon quantum dot-ferric oxide nanocomposite is obtained; according to the method, ferric oxide with a complex framework is compounded with the graphene carbon quantum dots, so that indoor VOCs can be oxidized at room temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanomaterials, and in particular to a carbon quantum dot-iron oxide nanocomposite material and a preparation method and application thereof. Background Art

[0002] In recent years, with the rapid development of the interior decoration industry, the extensive use of adhesives, paints and synthetic materials has led to the widespread presence of volatile organic compounds (VOCs), such as formaldehyde (HCHO), in indoor environments and their continued slow release. These VOCs molecules pose a potential threat to human health, and long-term exposure to such environments may induce chronic diseases. Although window ventilation is a traditional means of reducing VOCs concentration, its application is greatly limited in actual living environments, such as during noise interference or air conditioning use. Therefore, it is particularly important to develop efficient indoor VOCs removal technology. In chemical principles, oxygen in the air can react with VOCs to produce harmless CO2 and H2O, etc. This process is a spontaneous reaction in thermodynamics. However, due to the stability of VOCs molecules, the oxidation reaction kinetics at room temperature is extremely slow, which is difficult to meet the needs of practical applications. To this end, the introduction of catalysts to reduce the activation energy of VOCs molecular oxidation and accelerate the reaction process has become the key. However, the current VOCs oxidation catalysts and catalytic technologies have the following significant defects:

[0003] 1. High cost of precious metal catalysts: Precious metals such as platinum and palladium show excellent catalytic performance in many chemical reactions, but their scarcity leads to high prices. For large-scale VOCs oxidation treatment, the large-scale use of precious metal catalysts is economically unaffordable, limiting their widespread application;

[0004] 2. Strong dependence on photoelectric injection energy: Injecting energy into the catalytic reaction system through light or electricity can significantly increase the reaction rate. However, this method not only increases equipment costs and operating expenses, but may also cause the problem of increased by-products. In addition, the application of photoelectric catalytic technology is limited in certain indoor environments (such as areas without light sources or electricity);

[0005] 3. Residues of VOCs removal agents and health risks: Existing VOCs removal technologies on the market often use the method of spraying chemical reagents and then sealing the room. These reagents are often difficult to completely remove, and their residues may pose unknown risks to human health. The toxicity of some VOCs removal agents is even greater than the VOCs being removed, exacerbating the safety issues of use.

[0006] In view of the above records, the traditional VOCs removal methods have the disadvantages of high cost, low efficiency and environmental damage. Therefore, it is particularly important to develop an efficient, economical and environmentally friendly VOCs removal material. Summary of the invention

[0007] The purpose of the present invention is to provide a carbon quantum dot-iron oxide nanocomposite material, which uses a zeolite imidazolate skeleton structure material as a precursor to synthesize iron oxide with a complex framework, high specific surface area, and high catalytic activity, and composites it with graphene carbon quantum dots of 5-8nm size, so that it can oxidize indoor VOCs at room temperature. The VOCs in the test box can be removed by 83.5±4.3% within 24 hours of the experiment.

[0008] To achieve the above object, the present invention provides a carbon quantum dot-iron oxide nanocomposite material, which is prepared by the following steps:

[0009] S1: mixing ferrous sulfate solution and imidazole methanol solution and then ultrasonically treating to obtain a zeolite imidazole ester framework material containing an iron core;

[0010] S2: calcining the zeolite imidazolate framework material at a temperature range of 200-700° C. and an oxygen partial pressure of 5-40% to obtain iron oxide having a complex framework structure;

[0011] S3: Synthesize graphene carbon quantum dots with a size of 5-8 nm using the trinitrophenol method;

[0012] S4: After mixing the graphene carbon quantum dots and iron oxide powder, uniformly grinding them in a ball mill, the ball milling time is 60-240 min, and the content of the graphene carbon quantum dots added is 0.5-3wt%, to obtain a carbon quantum dot-iron oxide nanocomposite material.

[0013] Optionally, the concentration of the ferrous sulfate solution is 0.001-0.01 mol / L, the concentration of the imidazole methanol solution is 0.005-0.01 mol / L, and the mixing ratio of the ferrous sulfate solution and the imidazole methanol solution is 1:1-1:5.

[0014] Optionally, during the calcination process, the heating rate is 1-10°C / min, the calcination temperature is optimized according to the crystal form of the iron oxide and the required catalytic activity, and the control of the oxygen partial pressure during the calcination process is achieved through a precise gas flow control system.

[0015] Optionally, during the synthesis of the graphene carbon quantum dots, the weight ratio of trinitrophenol to graphene raw material is 1:100-1:1000, and the temperature during the synthesis is controlled at 120-220°C.

[0016] Optionally, during the ball milling process, the rotation speed of the ball mill is 200-500 rpm, the material and size of the ball milling medium are selected according to the physical properties of iron oxide and carbon quantum dots, and the mass ratio of the ball milling medium to the material is 10:1 to 20:1.

[0017] Optionally, during the dispersion process of the composite powder, the power of the ultrasonic treatment is 100-500w, the frequency of the ultrasound is adjusted according to the dispersion effect of the composite powder, and the frequency range of the ultrasonic treatment is 20-60kHz.

[0018] To achieve the above object, the present invention also provides a method for preparing the carbon quantum dot-iron oxide nanocomposite material, comprising the following steps:

[0019] S10: preparing a ferrous sulfate methanol solution with a concentration of 0.001-0.01 mol / L;

[0020] S20: prepare an imidazole methanol solution with a concentration of 0.005-0.01 mol / L;

[0021] S30: pouring the ferrous sulfate solution into the imidazole methanol solution under ultrasonication for 5-60 min;

[0022] S40: After sonication of the mixed solution, the solution was kept in the dark for 24 hours and then centrifuged, washed and dried;

[0023] S50: placing the dried powder obtained in S40 into a programmed temperature tube furnace, with a heating rate of 1-10°C / min, a calcination temperature of 200-700°C, a calcination time of 30-300min, a calcination oxygen partial pressure of 5-40%, and collecting the obtained iron oxide powder after natural cooling;

[0024] S60: Graphene carbon quantum dots are mixed with iron oxide powder and then uniformly ground in a ball mill. The microscopic size of the carbon quantum dots is 5-8 nm, the added content is 0.5-3 wt%, and the ball milling time is 60-240 min.

[0025] To achieve the above purpose, the present invention also provides a VOCs removal fiber cloth loaded with the carbon quantum dot-iron oxide nanocomposite material, wherein the carbon quantum dot-iron oxide nanocomposite material powder is dispersed using ethanol, and the dispersion concentration is 0.01-0.1 g / mL; the carbon fiber cloth is placed in the dispersion liquid, and the carbon fiber cloth is taken out after ultrasonic treatment for 5-60 minutes, and dried to obtain the VOCs removal fiber cloth.

[0026] Optionally, during the drying process of the carbon fiber cloth, the drying temperature is 40-60°C and the drying rate is 0.5-2.5 kg / m 2 / h, and a circulating hot air system is used during the drying process to ensure uniform drying.

[0027] To achieve the above object, the present invention also provides a method for catalytic oxidation of VOCs molecules using the VOCs removal fiber cloth, comprising the following steps:

[0028] a. Place the VOCs removal fiber cloth at the indoor fresh air outlet;

[0029] b. Utilize the VOCs removal fiber cloth to continuously catalyze and oxidize indoor VOCs at room temperature. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be understood by people with general skills in the field to which the present invention belongs. "Including" and similar words used in this article mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects.

[0031] In view of the problems existing in the prior art, an embodiment of the present invention provides a carbon quantum dot-iron oxide nanocomposite material, wherein the composite material is prepared by the following steps:

[0032] S1: The ferrous sulfate solution and the imidazole methanol solution are mixed and then ultrasonically treated to obtain a zeolite imidazole ester framework structure material containing an iron core.

[0033] Specifically, the ferrous sulfate solution is prepared: first, according to the experimental needs, a certain amount of ferrous sulfate is accurately weighed, dissolved in methanol, and prepared into a 0.001-0.01 mol / L solution; imidazole methanol solution is prepared: a certain amount of imidazole compounds are accurately weighed, and also dissolved in methanol to prepare a 0.005-0.01 mol / L solution; mixed solution: at room temperature, the ferrous sulfate solution is slowly added to the imidazole methanol solution, stirring while adding to ensure uniform mixing; ultrasonic treatment: the mixed solution is placed in an ultrasonic device for ultrasonic treatment, and the ultrasonic time is controlled at 5-60 min. Ultrasonic treatment helps to accelerate dissolution and mixing and promote the uniform formation of materials; light-proof and standing: after ultrasonic treatment, the solution is transferred to a light-proof environment and stood for 24 hours to complete the precipitation process; centrifugal washing and drying: after the precipitation is completed, centrifugal separation is performed using a centrifuge to remove the supernatant, and then the precipitate is washed with methanol and deionized water, and finally dried to obtain a zeolite imidazole ester framework structure material containing an iron core.

[0034] The zeolite imidazolate framework structure material obtained through the above step S1 has the following characteristics: high porosity and large specific surface area: zeolite imidazolate framework structure materials (similar to ZIFs) usually have high porosity and large specific surface area, which makes them have potential application value in gas adsorption, separation and catalysis. Metal-organic framework structure: this type of material is a porous crystalline structure formed by self-assembly of metal ions (iron in this case) and organic ligands (imidazole compounds); thermal stability: zeolite imidazolate framework structure materials usually have good thermal stability and can maintain their structural integrity at higher temperatures; chemical stability: due to the iron core, this type of material exhibits good chemical stability and can resist corrosion from a variety of chemical environments.

[0035] S2: calcining the zeolite imidazolate framework material at a temperature range of 200-700° C. and an oxygen partial pressure of 5-40% to obtain iron oxide having a complex framework structure;

[0036] Specifically, calcination: the obtained zeolite imidazolate skeleton structure material is placed in a tubular furnace and calcined at a temperature range of 200-700°C, and the oxygen partial pressure is controlled to be 5-40% during the calcination process. The calcination time is controlled to be 30-300 minutes; oxygen partial pressure control: the oxygen partial pressure can be achieved by controlling the oxygen flow in the furnace, and the oxygen partial pressure has a great influence on the crystal phase and microstructure of the material; natural cooling: after the calcination is completed, the furnace is closed, the sample is allowed to cool naturally to room temperature, and then taken out to obtain iron oxide with a complex framework structure.

[0037] After the above step S2, a complex framework structure can be formed: within the calcination temperature range of 200-700°C, iron oxide with a complex framework structure can be formed. This structure usually has a high specific surface area and porosity, which is conducive to the catalytic reaction, and can also enhance thermal stability: by calcining in an environment with an oxygen partial pressure of 5-40%, the thermal stability of iron oxide can be enhanced, so that it can still maintain a good structure and performance at a higher temperature, and at the same time, improve the catalytic performance: the calcination process helps to remove organic ligands and other volatile impurities in the zeolite imidazolate framework structure material, thereby exposing more active sites, improving the catalytic activity of iron oxide, and controlling the crystal phase: the control of calcination temperature and oxygen partial pressure helps to form iron oxide with a specific crystal phase (such as γ-iron oxide), and different crystal phases have different physical and chemical properties and catalytic activities and improve the specific surface area: the calcination process can produce iron oxide with a larger specific surface area, which helps to improve the adsorption capacity and catalytic efficiency of the material.

[0038] It should be noted that the complex framework structure of iron oxide has the following framework structure:

[0039] The obtained iron oxide is porous: there are a large number of micropores or mesopores inside the material, and these holes can increase the contact area of ​​the reactants and improve the catalytic efficiency; high specific surface area: the catalyst per unit mass has a large surface area, which helps to provide more active sites; layered or cage-like structure: the iron oxide structure presents a layered or cage-like structure, which can capture and concentrate reactants, thereby promoting catalytic reactions; nano-sized particles: the iron oxide particles are very small (nanoscale), which also helps to increase the surface area and activity of the catalyst; specific crystal morphology: the control of calcination temperature and oxygen partial pressure helps to form iron oxide with a specific crystal form, and these different crystal forms have different physical and chemical properties and catalytic activities. The crystal forms of iron oxide include α-iron oxide type and γ-iron oxide type, among which α-iron oxide type presents a hexagonal crystal structure with high thermal stability and good catalytic activity. Compared with α-iron oxide type, γ-iron oxide type has the advantage of activating molecular oxygen under mild conditions; but it is not limited to α-iron oxide type and γ-iron oxide type.

[0040] S3: Synthesize graphene carbon quantum dots with a size of 5-8 nm using the trinitrophenol method;

[0041] Specifically, the trinitrophenol method: graphene oxide and trinitrophenol are mixed in a solvent, and then heated to a certain temperature for reaction. By controlling the reaction conditions, graphene carbon quantum dots with a size of 5-8nm can be synthesized; characterization of carbon quantum dots: the synthesized graphene carbon quantum dots are characterized by high-resolution transmission electron microscopy (HRTEM), atomic force microscopy (AFM) and other means to ensure that the size is within the range of 5-8nm.

[0042] Step S3 can maintain the uniformity of graphene carbon quantum dots size: the trinitrophenol method can be used to synthesize carbon quantum dots of uniform size, which helps to ensure the consistency and repeatability of the material; surface functionalization: the surface of carbon quantum dots synthesized by the trinitrophenol method is easy to functionalize and can be further modified to enhance its performance or introduce new functions.

[0043] S4: After mixing the carbon quantum dots and iron oxide powder, uniformly grinding them in a ball mill, the ball milling time is 60-240 min, and the content of the graphene carbon quantum dots added is 0.5-3wt%, to obtain a carbon quantum dot-iron oxide nanocomposite material.

[0044] Specifically, mixing: the synthesized graphene carbon quantum dots and iron oxide powder are mixed evenly in a certain proportion; ball milling: the mixed powder is put into a ball mill for ball milling, and the ball milling time is controlled at 60-240 minutes. The material and size of the ball milling medium should be selected according to the physical properties of iron oxide and carbon quantum dots; screening: after the ball milling, the powder is screened to ensure the uniformity and fineness of the composite material; graphene carbon quantum dot content: the addition amount of graphene carbon quantum dots is controlled at 0.5-3wt%, and this ratio can be adjusted according to experimental needs to achieve the best catalytic performance.

[0045] After step S4, the stability can be enhanced: the introduction of graphene carbon quantum dots can improve the photochemical stability of iron oxide, so that the composite material can still maintain good catalytic performance after repeated use; the specific surface area can be increased: the ball milling process helps to increase the specific surface area of ​​the material, providing more active sites for the reaction, thereby improving the catalytic efficiency; a controllable composite material structure can be obtained: by adjusting the ball milling time and the amount of carbon quantum dots added, the structure and performance of the composite material can be regulated to meet different application requirements.

[0046] In summary, through the above steps S1, S2, S3 and S4, it can be concluded that the present invention uses zeolite imidazolate skeleton structure material as a precursor to synthesize iron oxide with a complex framework, high specific surface area and high catalytic activity, and composites it with graphene carbon quantum dots of 5-8nm size, so that it can oxidize indoor VOCs molecules at room temperature. Within 24 hours of the experiment, 83.5±4.3% of the VOCs in the test box can be removed.

[0047] In one embodiment, the concentration of the ferrous sulfate solution is 0.001-0.01 mol / L, the concentration of the imidazole methanol solution is 0.005-0.01 mol / L, and the mixing ratio of the ferrous sulfate solution and the imidazole methanol solution is 1:1-1:5.

[0048] In this embodiment, the concentration of the ferrous sulfate solution is controlled to 0.001-0.01mol / L, and the concentration of the imidazole methanol solution is controlled to be within the range of 0.005-0.01mol / L, so that both can be guaranteed to fully react to form the required compound structure, and at the same time, the concentration of ferrous sulfate solution and imidazole methanol solution can also increase the collision chance between reactant molecules within the above range, so as to improve the reaction rate. The mixing ratio of the ferrous sulfate solution and the imidazole methanol solution is 1:1-1:5, which can significantly improve the dissolution and mixing uniformity of ferrous sulfate solution and imidazole methanol solution, and at the same time, it is also helpful to improve the solubility and mixing uniformity of the reactant. At the same time, by the concentration of the ferrous sulfate solution and the imidazole methanol solution described above, and the mixing ratio, the occurrence of side reactions can be reduced, and the selectivity of the target product is guaranteed.

[0049] In one embodiment, during the calcination process, the heating rate is 1-10°C / min, the calcination temperature is optimized according to the crystal form of the iron oxide and the required catalytic activity, and the control of the oxygen partial pressure during the calcination process is achieved through a precise gas flow control system.

[0050] The configuration of this embodiment can accurately control the transformation of the crystal form: the calcination temperature has an important influence on the crystal form and phase change of iron oxide. Accurate control of the calcination temperature can promote the formation of the desired crystal form, thereby optimizing the physical and chemical properties of the material; can improve the catalytic activity: by optimizing the calcination temperature and the oxygen partial pressure, the catalytic activity of iron oxide can be improved and its efficiency in various chemical reactions can be enhanced; can control the specific surface area: the precise control of the calcination temperature helps to regulate the crystal growth and pore structure of iron oxide, thereby affecting its specific surface area, which is crucial to the performance of the catalyst; avoid over-sintering: the slow heating rate helps to avoid over-sintering of the material and maintain its porous structure, which is very beneficial for maintaining high catalytic activity and good mass transfer characteristics.

[0051] In one embodiment, during the synthesis of the graphene carbon quantum dots, the weight ratio of trinitrophenol to the synthesis solvent is 1:100-1:1000, and the temperature during the synthesis is controlled at 120-220°C.

[0052] This embodiment can accurately control the size of carbon quantum dots: by controlling the ratio of trinitrophenol to the synthetic solvent, the size of graphene carbon quantum dots can be effectively controlled, thereby obtaining a more consistent nanoparticle size distribution; the uniformity of the reaction can be improved: carrying out the reaction at a slightly higher temperature (120-220°C) can increase the movement speed of the reactant molecules, making the dispersion of trinitrophenol in the synthetic solvent more uniform, which helps to form uniform carbon quantum dots.

[0053] In one embodiment, during the ball milling process, the rotation speed of the ball mill is 200-500 rpm, the material and size of the ball milling medium are selected according to the physical properties of iron oxide and carbon quantum dots, and the mass ratio of the ball milling medium to the material is 10:1 to 20:1.

[0054] The setting of this embodiment can improve the grinding efficiency: the appropriate rotation speed can ensure sufficient impact and friction between the ball milling medium and the material, thereby improving the grinding efficiency and avoiding over-grinding, such as 200-500rpm: the moderate rotation speed avoids the ball milling medium from moving too fast and reduces the risk of the material being over-grinded into too fine powder, such as 300rpm; it can ensure uniform grinding: the mass ratio of the ball milling medium to the material is 10:1 to 20:1, which is conducive to increasing the grinding contact area and improving the grinding uniformity; at the same time, the material morphology is controlled: selecting the appropriate ball milling medium size can help control the morphology and particle size distribution of the ground material.

[0055] In one embodiment, during the dispersion process of the composite powder, the power of the ultrasonic treatment is 100-500 watts, the frequency of the ultrasound is adjusted according to the dispersion effect of the composite powder, and the frequency range of the ultrasonic treatment is 20-60 kHz.

[0056] The configuration of this embodiment can improve the dispersion uniformity: ultrasonic treatment can effectively disperse and break up the agglomerates in the powder through the shock waves and local high temperature and high pressure generated by the cavitation effect, thereby improving the dispersion uniformity of the powder and promoting the cleaning of the particle surface: ultrasonic vibration acts on the powder particles to remove impurities and adsorbents on the particle surface, improve the cleanliness of the particle surface, and improve the compatibility of the particles with the medium: ultrasonic treatment can improve the compatibility between the particles and the medium, enhance the stability of the dispersion system and enhance the interaction between the particles: ultrasonic vibration can promote the interaction between the particles and help form a more stable composite material.

[0057] In view of the problems existing in the prior art, an embodiment of the present invention further provides a method for preparing the carbon quantum dot-iron oxide nanocomposite material, comprising the following steps:

[0058] S10: preparing a ferrous sulfate methanol solution with a concentration of 0.001-0.01 mol / L;

[0059] S20: prepare an imidazole methanol solution with a concentration of 0.005-0.01 mol / L;

[0060] S30: pouring the ferrous sulfate solution into the imidazole methanol solution under ultrasonication for 5-60 min;

[0061] S40: After sonication of the mixed solution, the solution was kept in the dark for 24 hours and then centrifuged, washed and dried;

[0062] S50: placing the dried powder obtained in S40 into a programmed temperature tube furnace, with a heating rate of 1-10°C / min, a calcination temperature of 200-700°C, a calcination time of 30-300min, a calcination oxygen partial pressure of 5-40%, and collecting the obtained iron oxide powder after natural cooling;

[0063] S60: Graphene carbon quantum dots are mixed with iron oxide powder and then uniformly ground in a ball mill. The microscopic size of the carbon quantum dots is 5-8 nm, the added content is 0.5-3 wt%, and the ball milling time is 60-240 min.

[0064] In view of the problems existing in the prior art, an embodiment of the present invention further provides a VOCs removal fiber cloth loaded with the carbon quantum dot-iron oxide nanocomposite material, wherein the carbon quantum dot-iron oxide nanocomposite material powder is dispersed using ethanol, and the dispersion concentration is 0.01-0.1 g / mL; the carbon fiber cloth is placed in the dispersion liquid, and the carbon fiber cloth is taken out after ultrasonic treatment for 5-60 minutes, and dried to obtain the VOCs removal fiber cloth.

[0065] The configuration of this embodiment can improve dispersibility: ethanol is a commonly used solvent that can dissolve and disperse a variety of substances well. Ultrasonic treatment can further break up the powder particles to avoid agglomeration, thereby obtaining a more uniform dispersion; it can enhance wettability: ethanol can increase the contact area between the fiber and the powder, improve wettability, and help the powder to adhere more evenly to the carbon fiber cloth; it can promote penetration: the vibration energy generated by ultrasonic treatment helps the dispersion to penetrate into the pores of the carbon fiber cloth, thereby enhancing the bonding force between the materials; it can increase the reaction rate: ultrasonic vibration can accelerate chemical reactions, shorten preparation time, and improve production efficiency; it can enhance interface bonding: ultrasonic treatment helps to enhance the interface bonding between the carbon fiber cloth and the carbon quantum dot-iron oxide nanocomposite material dispersed thereon, thereby improving the overall performance of the composite material.

[0066] In one embodiment, during the drying process of the carbon fiber cloth, the drying temperature is 40-60°C and the drying rate is 0.5-2.5 kg / m 2 / h, and a circulating hot air system is used during the drying process to ensure uniform drying.

[0067] The configuration of this embodiment can provide mild drying conditions: the drying temperature of 40-60°C is a relatively mild range, which avoids the damage that high temperature may cause to the carbon fiber cloth, such as excessive shrinkage or thermal degradation of the material; it can achieve uniform drying effect: the circulating hot air system can ensure that the hot air is evenly distributed in the drying room, ensuring that all parts of the carbon fiber cloth are evenly dried, thereby preventing local overheating or uneven drying; it can accurately control the drying rate: the drying rate is 0.5-2.5kg / m 2 / h can be adjusted according to actual needs, which helps to control the moisture removal rate of the material during the drying process and ensure the consistency of material properties.

[0068] In view of the problems existing in the prior art, an embodiment of the present invention further provides a catalytic oxidation method using the VOCs removal fiber cloth, comprising the following steps:

[0069] a. Place the VOCs removal fiber cloth at the indoor fresh air outlet;

[0070] b. Utilize the VOCs removal fiber cloth to continuously catalyze and oxidize indoor VOCs molecules at room temperature.

[0071] The arrangement of this embodiment can purify VOCs efficiently: the VOCs removal fiber cloth can continuously catalyze and oxidize indoor VOCs at room temperature, which can effectively reduce the indoor VOCs concentration and improve the indoor air quality; no additional energy consumption is required: the catalytic reaction can be carried out at room temperature, and no additional heat or light energy input is required, saving energy; lasting effect: the VOCs removal fiber cloth can act sustainably, purify indoor air for a long time, and provide lasting protection; safety: it avoids the use of harmful substances or methods, such as some chemical sprays that may be harmful to human health, while the method of the present invention is safe and environmentally friendly; convenient maintenance: the VOCs removal fiber cloth is easy to install and replace, and the user can operate it by themselves, which is simple to maintain; economical and practical: compared with purification methods that require expensive equipment or complex operations, the method of the present invention is low-cost and easy to popularize.

[0072] The carbon quantum dot-iron oxide nanocomposite material and its application are described in detail below through specific embodiments:

[0073] Example 1

[0074] Preparation of Carbon Quantum Dots-Iron Oxide Nanocomposites

[0075] S1: mixing ferrous sulfate solution and imidazole methanol solution and then ultrasonically treating to obtain a zeolite imidazole ester framework material containing an iron core;

[0076] S2: calcining the zeolite imidazolate framework material at a temperature range of 600° C. and an oxygen partial pressure of 20% to obtain iron oxide having a complex framework structure;

[0077] S3: Synthesize graphene carbon quantum dots with a size of 4 nm using the trinitrophenol method;

[0078] S4: The graphene carbon quantum dots and iron oxide powder are mixed and then uniformly ground in a ball mill. The ball milling time is 60 minutes. The content of the carbon quantum dots added is 0.5 wt % to obtain a carbon quantum dot-iron oxide nanocomposite material.

[0079] Example 2

[0080] Methods for carbon quantum dot-iron oxide nanocomposites

[0081] S10: prepare ferrous sulfate methanol solution with a concentration of 0.001 mol / L;

[0082] S20: prepare an imidazole methanol solution with a concentration of 0.005 mol / L;

[0083] S30: pouring the ferrous sulfate solution into the imidazole methanol solution under ultrasonication for 5 min;

[0084] S40: After sonication of the mixed solution, the solution was kept in the dark for 24 hours and then centrifuged, washed and dried;

[0085] S50: placing the dried powder obtained in S40 into a programmed temperature tube furnace, heating at a rate of 1°C / min, calcining at 500°C, calcining for 30-300min, calcining at an oxygen partial pressure of 5%, and collecting the obtained iron oxide powder after natural cooling;

[0086] S60: Graphene carbon quantum dots are mixed with iron oxide powder and then uniformly ground in a ball mill. The microscopic size of the carbon quantum dots is 4 nm, the added content is 0.5 wt%, and the ball milling time is 60 min.

[0087] Example 3

[0088] Preparation of VOCs removal fiber cloth

[0089] A VOCs removal fiber cloth loaded with the carbon quantum dot-iron oxide nanocomposite material is prepared by using ethanol to disperse the carbon quantum dot-iron oxide nanocomposite material powder with a dispersion concentration of 0.01 g / mL; placing the carbon fiber cloth in the dispersion liquid, ultrasonically treating the carbon fiber cloth for 5 minutes, taking out the carbon fiber cloth, and drying the carbon fiber cloth to obtain the VOCs removal fiber cloth.

[0090] Comparative Example

[0091] Comparative Example 1: Using traditional activated carbon as the control material, the initial VOCs concentration was also 500 ppb. After 24 hours of treatment, the VOCs concentration dropped to 300 ppb, and the removal rate was 40%.

[0092] Comparative Example 2: Commercially available photocatalysts were used to remove VOCs. The initial concentration was 500 ppb. After 24 hours of treatment, the VOCs concentration dropped to 250 ppb, and the removal rate was 50%.

[0093] Table 1 Summary of experimental data

[0094]

[0095] Through the experimental data of the above-mentioned Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2, it can be seen that the carbon quantum dot-iron oxide nanocomposite material exhibits excellent removal effect in indoor VOCs purification, which is significantly better than traditional activated carbon and commercially available photocatalysts. This shows that the material of the present invention has good application prospects and can effectively improve indoor air quality.

[0096] Comparative Example 3

[0097] Using platinum catalyst as the control material, the initial VOCs concentration was also 500 ppb. After 24 hours of treatment, the VOCs concentration dropped to 100 ppb, with a removal rate of 80%. The purchase of 100g of platinum catalyst cost 1,000 yuan.

[0098] Table 2 Comparison of efficiency and cost of noble metal catalysts and carbon quantum dots-iron oxide nanocomposites

[0099]

[0100] Through the experimental data of the above Example 1 and Comparative Example 3, it can be seen that the catalytic efficiency of the carbon quantum dot-iron oxide nanocomposite material in indoor VOCs is not much different from that of the platinum catalyst, but in the case of the same amount, the purchase cost of the platinum catalyst is greater than the preparation cost of the carbon quantum dot-iron oxide nanocomposite material. This shows that the carbon quantum dot-iron oxide nanocomposite material of the present invention has a good price advantage.

[0101] Example 4

[0102] Preparation of Carbon Quantum Dots-Iron Oxide Nanocomposites

[0103] S1: mixing ferrous sulfate solution and imidazole methanol solution and then ultrasonically treating to obtain a zeolite imidazole ester framework material containing an iron core;

[0104] S2: calcining the zeolite imidazolate framework material at a temperature range of 600° C. and an oxygen partial pressure of 20% to obtain iron oxide having a complex framework structure;

[0105] S3: Synthesize graphene carbon quantum dots with a size of 5 nm using the trinitrophenol method;

[0106] S4: The carbon quantum dots and iron oxide powder are mixed and then uniformly ground in a ball mill. The ball milling time is 60 min. The content of the carbon quantum dots added is 0.5 wt % to obtain a carbon quantum dot-iron oxide nanocomposite material.

[0107] Example 5

[0108] Preparation of Carbon Quantum Dots-Iron Oxide Nanocomposites

[0109] S1: mixing ferrous sulfate solution and imidazole methanol solution and then ultrasonically treating to obtain a zeolite imidazole ester framework material containing an iron core;

[0110] S2: calcining the zeolite imidazolate framework material at a temperature range of 600° C. and an oxygen partial pressure of 20% to obtain iron oxide having a complex framework structure;

[0111] S3: Synthesize graphene carbon quantum dots with a size of 6 nm using the trinitrophenol method;

[0112] S4: The carbon quantum dots and iron oxide powder are mixed and then uniformly ground in a ball mill. The ball milling time is 60 min. The content of the carbon quantum dots added is 0.5 wt % to obtain a carbon quantum dot-iron oxide nanocomposite material.

[0113] Example 6

[0114] Preparation of Carbon Quantum Dots-Iron Oxide Nanocomposites

[0115] S1: mixing ferrous sulfate solution and imidazole methanol solution and then ultrasonically treating to obtain a zeolite imidazole ester framework material containing an iron core;

[0116] S2: calcining the zeolite imidazolate framework material at a temperature range of 600° C. and an oxygen partial pressure of 20% to obtain iron oxide having a complex framework structure;

[0117] S3: Synthesize graphene carbon quantum dots with a size of 8 nm using the trinitrophenol method;

[0118] S4: The carbon quantum dots and iron oxide powder are mixed and then uniformly ground in a ball mill. The ball milling time is 60 min. The content of the carbon quantum dots added is 0.5 wt % to obtain a carbon quantum dot-iron oxide nanocomposite material.

[0119] Example 7

[0120] Preparation of Carbon Quantum Dots-Iron Oxide Nanocomposites

[0121] S1: mixing ferrous sulfate solution and imidazole methanol solution and then ultrasonically treating to obtain a zeolite imidazole ester framework material containing an iron core;

[0122] S2: calcining the zeolite imidazolate framework material at a temperature range of 600° C. and an oxygen partial pressure of 20% to obtain iron oxide having a complex framework structure;

[0123] S3: Synthesis of graphene carbon quantum dots with a size of 9 nm using the trinitrophenol method;

[0124] S4: The carbon quantum dots and iron oxide powder are mixed and then uniformly ground in a ball mill. The ball milling time is 60 min. The content of the carbon quantum dots added is 0.5 wt % to obtain a carbon quantum dot-iron oxide nanocomposite material.

[0125] Table 3 Effect of graphene carbon quantum dot size on VOCs removal

[0126]

[0127] Through the experimental data of the above examples 1, 4, 5, 6 and 7, it can be seen that the graphene carbon quantum dots with a size of 5-8nm have a VOCs removal effect that is significantly better than the graphene carbon quantum dots with a size greater than 8nm and less than 5nm. This indicates that the graphene carbon quantum dots with a size of 5-8nm have higher catalytic performance.

[0128] Example 7

[0129] Carbon quantum dots-iron oxide composite decoration additive

[0130] The composite material can be added to paint or putty powder at a ratio of 0.3-0.7 wt %, and can be retained on the wall or furniture surface during the decoration process to continuously oxidize and decompose the emitted VOCs.

[0131] Example 8

[0132] Carbon quantum dots-iron oxide composite VOCs removal paper

[0133] Disperse the above composite material with water and spray it evenly on paper at a concentration of 0.1 to 0.3 g / mL. After drying naturally, place it in a locker or furniture to continuously purify the internal air and decompose VOCs.

[0134] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.

Claims

1. A carbon quantum dot-iron oxide nanocomposite material, characterized in that: The composite material is prepared by the following steps: S1: mixing ferrous sulfate solution and imidazole methanol solution and then ultrasonically treating to obtain a zeolite imidazole ester framework material containing an iron core; S2: calcining the zeolite imidazolate framework material at a temperature range of 200-700° C. and an oxygen partial pressure of 5-40% to obtain iron oxide having a complex framework structure; S3: Synthesize graphene carbon quantum dots with a size of 5-8 nm using the trinitrophenol method; S4: After mixing the graphene carbon quantum dots and iron oxide powder, uniformly grinding them in a ball mill, the ball milling time is 60-240 min, and the content of the graphene carbon quantum dots added is 0.5-3wt%, to obtain a carbon quantum dot-iron oxide nanocomposite material.

2. The carbon quantum dot-iron oxide nanocomposite material according to claim 1, characterized in that: The concentration of the ferrous sulfate solution is 0.001-0.01 mol / L, the concentration of the imidazole methanol solution is 0.005-0.01 mol / L, and the mixing ratio of the ferrous sulfate solution and the imidazole methanol solution is 1:1-1:

5.

3. The carbon quantum dot-iron oxide nanocomposite material according to claim 1, characterized in that: During the calcination process, the heating rate is 1-10°C / min.

4. The carbon quantum dot-iron oxide nanocomposite material according to claim 1, characterized in that: During the synthesis of the graphene carbon quantum dots, the weight ratio of trinitrophenol to graphene raw material is 1:100-1:1000, and the temperature during the synthesis is controlled at 120-220°C.

5. The carbon quantum dot-iron oxide nanocomposite material according to claim 1, characterized in that: During the ball milling process, the rotation speed of the ball mill is 200-500 rpm, and the mass ratio of the ball milling medium to the material is 10:1 to 20:

1.

6. The carbon quantum dot-iron oxide nanocomposite material according to claim 1, characterized in that: During the dispersion of the composite powder, the power of the ultrasonic treatment is 100-500w, and the frequency range of the ultrasonic treatment is 20-60kHz.

7. A method for preparing the carbon quantum dot-iron oxide nanocomposite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S10: prepare ferrous sulfate methanol solution with a concentration of 0.001-0.01 mol / L; S20: prepare an imidazole methanol solution with a concentration of 0.005-0.01 mol / L; S30: pouring the ferrous sulfate solution into the imidazole methanol solution under ultrasonication for 5-60 min; S40: After sonication of the mixed solution, the solution was kept in the dark for 24 hours and then centrifuged for washing and drying; S50: placing the dried powder obtained in S40 into a programmed temperature tube furnace, with a heating rate of 1-10°C / min, a calcination temperature of 200-700°C, a calcination time of 30-300min, a calcination oxygen partial pressure of 5-40%, and collecting the obtained iron oxide powder after natural cooling; S60: Graphene carbon quantum dots are mixed with iron oxide powder and then ground evenly in a ball mill. The microscopic size of the carbon quantum dots is 5-8 nm, the added content is 0.5-3 wt%, and the ball milling time is 60-240 min.

8. A VOCs removal fiber cloth loaded with the carbon quantum dot-iron oxide nanocomposite material according to any one of claims 1 to 6, characterized in that: Ethanol is used to disperse carbon quantum dot-iron oxide nanocomposite powder at a dispersion concentration of 0.01-0.1 g / mL; carbon fiber cloth is placed in the dispersion liquid, and after ultrasonic treatment for 5-60 minutes, the carbon fiber cloth is taken out and dried to obtain VOCs removal fiber cloth.

9. The VOCs removal fiber cloth according to claim 8, characterized in that: During the drying process of the carbon fiber cloth, the drying temperature is 40-60°C and the drying rate is 0.5-2.5kg / m 2 / h, and a circulating hot air system is used during the drying process to ensure uniform drying.

10. A catalytic oxidation method using the VOCs removal fiber cloth according to claim 8, characterized in that: The following steps are involved: a. Place the VOCs removal fiber cloth at the indoor fresh air outlet; b. Utilize the VOCs removal fiber cloth to continuously catalyze and oxidize indoor VOCs molecules at room temperature.

Citation Information

Cited By

  • Graphene quantum dot loaded iron-doped titanium-based metal organic framework photocatalyst as well as preparation method and application thereof

    CN117696119A

  • A graphene quantum dot-loaded iron-doped titanium-based metal-organic framework photocatalyst, its preparation method and application

    CN117696119B

  • Nano-composite insulating material, insulated cable and insulation defect repairing robot

    CN121075770A